“Nothing replaces meeting my students at class”: Analysing academics’ views regarding distance education - GEÇER, EKMEL (My University, 2023)
Distance education, also called distance learning, e-learning, and online learning, is a practice of teaching and learning in which teachers and learners are not in a closed class or room in person, but where education takes place through various new-media technologies and all parties (student–teacher, teacherteacher, student–student) are able to communicate, interact and exchange information and emotions. Being on the agenda of educational science for a long time now and gaining further importance during COVID-19 lockdowns, both advantages (e.g., reducing social anxiety, and a flexible schedule) and disadvantages (lack of social interactivity, and miscommunication) of distance education are highly debated in the related literature. Therefore, this study, through a qualitative method (i.e., a case study design and semi-structured interviews), aims to analyse the opinions and experiences of academics regarding distance education and its applications. The participants consist of 36 lecturers working at 16 different Turkish universities selected by the purposeful sampling method (i.e., typical case sampling). The results suggest that the participants still have doubts about online distance education, and they mention both ups (ease of connection, and cost-effectiveness) and downs (lack of self-motivation, socialization, and the sense of isolation) of it. Nonetheless, none of the academics thinks distance education will replace an in-person learning environment in the near future. Thus, this study presents a general illustration of distance education activities through the views of Turkish academics and gives recommendations for future digital/distance/online learning activities and functionalities.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; Eğitim; Social Sciences and Humanities; Psychology; Social Psychology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, SOSYAL; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, SOCIAL; EDUCATION & EDUCATIONAL RESEARCH; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Distance education; Academic motivation; Social connection; Turkey